Գրաբարի ձեւաբանական կարգերը Մ. Աբեղեանի դիտարկմամբ - Իւբաշեան, Անահիտ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
М. Абегян подчеркивает важность морфологических и синтаксических признаков частей речи. Он различает части речи и частицы. В работе представлены морфологические категории классического грабара (древнеармянского языка), их характерные нормы и исключения по работам М. Абегяна, посвященные изучению грабара. M. Abeghyan emphasizes the importance of morphological and syntactic features of parts of speech. He distinguishes between parts of speech and grammatical particles. The paper presents the morphological categories of the Classical Armenian language, their characteristic norms and exceptions based on the works of M. Abeghyan dedicated to the study of the Classical Armenian language.
Keywords: Morphology; Armenian language